Cash Receipts and Disbursements Accounting Information System at an Education Center - Amalia, Mekar Meilisa; Siahaan, Denny Lestari (Indonesian Journal of Sustainability Policy and Technology, 2024)
An information system integrates people, hardware, software, and data networks that continuously interact to store, collect, process, and distribute information to achieve organizational goals. An accounting information system is designed to collect, record, store, and process data from routine accounting transactions. The object of this research is Victory Education Center, which operates as a non-formal education service provider. This research aims to understand the accounting information system for cash receipts and disbursements applied by Victory Education Center, to determine whether the system is implemented according to procedures, and to identify methods to prevent cash fraud and embezzlement at Victory Education Center. In this study, the author uses a descriptive analysis method. The data sources include both primary and secondary data. The results show that the accounting information system for cash receipts and disbursements still relies on Microsoft Excel, which affects the accuracy of financial data and increases the time required to prepare financial reports for Victory Education Center. Additionally, no cash receipts and disbursement plans are in place, making it impossible to predict the annual cash inflows and outflows. Human resources are not optimally utilized, as some staff are working outside their areas of expertise, there is no segregation of duties between those receiving cash and those recording transactions, and financial reports are not audited because no specific department is assigned to perform such audits.